Investigation of the Impact of Point Defects in InGaN/GaN Quantum Wells with High Dislocation Densities - Pierre Lottigier; Davide Maria Di Paola; Duncan T. L. Alexander; Thomas F. K. Weatherley; Pablo Sáenz de Santa María Modroño; Danxuan Chen; Gwénolé Jacopin; Jean-François Carlin; Raphaël Butté; Nicolas Grandjean (Nanomaterials, 2023)
In this work, we report on the efficiency of single InGaN/GaN quantum wells (QWs) grown on thin (<1 µm) GaN buffer layers on silicon (111) substrates exhibiting very high threading dislocation (TD) densities. Despite this high defect density, we show that QW emission efficiency significantly increases upon the insertion of an In-containing underlayer, whose role is to prevent the introduction of point defects during the growth of InGaN QWs. Hence, we demonstrate that point defects play a key role in limiting InGaN QW efficiency, even in samples where their density (2–3 × 10<semantics>9</semantics> cm<semantics>−2</semantics>) is much lower than that of TD (2–3 × 10<semantics>10</semantics> cm<semantics>−2</semantics>). Time-resolved photoluminescence and cathodoluminescence studies confirm the prevalence of point defects over TDs in QW efficiency. Interestingly, TD terminations lead to the formation of independent domains for carriers, thanks to V-pits and step bunching phenomena.